The Effects of Immigration on NHS Waiting Times - Osea Giuntella; Catia Nicodemo; Carlos Vargas-Silva (Institute for the Study of Labor (IZA), 2015)
This paper analyses the effects of immigration on waiting times in the National Health Service (NHS) in England. Linking administrative records from the Hospital Episode Statistics (2003-2012) with immigration data drawn from the UK Labour Force Survey, we find that immigration reduced waiting times for outpatient referrals and did not have significant effects on waiting times in Accident and Emergency (A&E) and elective care. These results are explained by the fact that immigration increases natives' internal mobility and that immigrants tend to be healthier than the natives moving to different areas. On the contrary, we show that outpatient waiting times tend to increase in areas where native internal migrants moved into. Finally, we find evidence that immigration increased waiting times for outpatient referrals in more deprived areas outside London. The increase in average waiting times in more deprived areas is concentrated in the years immediately following the 2004 EU enlargement and vanished in the medium-run (e.g., 3 to 4 years).
Keywords: I10; J61; 330; immigration; waiting times; NHS; access to health care; welfare